2017
DOI: 10.1016/j.cell.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Proteome Remodeling and Aggregation in Aging C. elegans

Abstract: In Table S3B of the above article, protein identifiers were inadvertently matched with the wrong values. Table S3B reports a subset of data from Table S1, calculated as protein abundance values relative to day 1 of worm age. Note that, in Table S1, the values are displayed correctly. A corrected version of the Table S3B is available with this Correction online. The error does not affect the conclusions in the study, and we apologize for any inconvenience that it may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
219
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(249 citation statements)
references
References 0 publications
26
219
1
3
Order By: Relevance
“…The ageassociated increase in SQST-1, which is the C. elegans homologue of the elegans autophagosome cargo protein p62, also supports a late-life dysfunctional autophagic machinery in worms. This is also in agreement with the widespread protein aggregation during C. elegans ageing [60,61]. We additionally noted that genes crucially involved in the late autophagic flux at the steps of autolysosome formation and degradation are dispensable in aged worms.…”
Section: Age-related Changes In Autophagysupporting
confidence: 88%
See 1 more Smart Citation
“…The ageassociated increase in SQST-1, which is the C. elegans homologue of the elegans autophagosome cargo protein p62, also supports a late-life dysfunctional autophagic machinery in worms. This is also in agreement with the widespread protein aggregation during C. elegans ageing [60,61]. We additionally noted that genes crucially involved in the late autophagic flux at the steps of autolysosome formation and degradation are dispensable in aged worms.…”
Section: Age-related Changes In Autophagysupporting
confidence: 88%
“…A recent proteomic study revealed that daf-2 mutants employ enhanced 'waste management' strategies with age. Compared to aged WT worms, autophagy is neither systematically upregulated nor functionally enhanced in aged daf-2 mutants [59,60]. In contrast, daf-2 mutants enhance the UPS earlier and more pronounced during ageing than their WT counterpart [60].…”
Section: Regulation Of Autophagy In Longevitymentioning
confidence: 80%
“…Indeed, it has been recently shown that sequestering proteins into chaperone‐enriched aggregates prevents an age‐related decline in proteostasis and prolongs lifespan in C. elegans (Walther et al . ). Thus, HSPs may play an active role in the formation of the inclusions, rather than merely being a part of them as a fall‐out of their formation.…”
Section: The Role Of Molecular Chaperones In Neurodegenerative Diseasementioning
confidence: 97%
“…It is commonly thought that an age‐related impairment of protein degradation affects general proteostasis networks, causing enhanced accumulation of damaged proteins that can be cytotoxic and shortens lifespan . During aging, the cellular proteostasis network shows significant changes in expression, mainly causing an overall reduction in protein synthesis, which reflects age‐dependent remodeling of an imbalanced proteome . Progressive decline of proteostasis can lead to the development of various diseases .…”
Section: Discussionmentioning
confidence: 99%